Prevalence of the Cusp of Carabelli: a systematic review and meta-analysis - R. Bhavyaa; P. Sujitha; M. S. Muthu; Latha Nirmal; Sneha S. Patil (Taylor & Francis Group, 2021)
Context The Cusp of Carabelli (CoC) is the most commonly occurring dental morphological trait. Objective To provide a pancontinental overview on the prevalence of the CoC in primary maxillary second molars and permanent maxillary molars. Methods An electronic search was conducted on ten databases without year restrictions up to July 2020. All cross-sectional studies published in the English language reporting prevalence estimate of CoC were included. A modified version of the Newcastle-Ottawa scale was used to assess study quality. Meta-analyses were conducted for studies that reported data using Dahlberg and ASUDAS classification across continents. Results For qualitative synthesis, 142 studies (45,327 participants) were included, of which 130 studies had moderate risk of bias. Random effects meta-analysis was performed for 41 studies. For prevalence of CoC in primary maxillary second molars, the estimate was 72% (2,829 participants). The overall percentage attained for permanent maxillary molars was 59% (16,607 participants) for first molars; 8% (2,277 participants) for second molars; and 10% (89 participants) for third molars. Subgroup analysis revealed the European continent reported the highest prevalence in permanent maxillary first and second molars. Conclusion Primary maxillary second molars recorded highest prevalence of CoC followed by permanent maxillary first, third and second molars. Pancontinental studies with regard to primary maxillary second molars are warranted.